2019
DOI: 10.1186/s40643-019-0245-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and engineering electrochemically active bacteria for sustainable biotechnology

Abstract: Electrochemically active bacteria (EAB) receive considerable attention in sustainable biotechnology, since they are essential components in microbial fuel cells (MFCs) that are able to generate electricity from biomass wastes. EAB are also expected to be applied to the production of valued chemicals in microbial electrosynthesis systems (MESs) with the supply of electric energy from electrodes. It is, therefore, important to deepen our understanding of EAB in terms of their physiology, genetics and genomics. K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 144 publications
0
29
0
Order By: Relevance
“…In another study, Hirose et al (2019) showed how electrochemically active bacteria (EAB) can be a promising technology for energy-generation electricity from biomass. After conducting a laboratory study of the Shewanella oneidensis MR1, the authors found that this bacterium was able to generate and conserve electrical power in different growth phases.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Hirose et al (2019) showed how electrochemically active bacteria (EAB) can be a promising technology for energy-generation electricity from biomass. After conducting a laboratory study of the Shewanella oneidensis MR1, the authors found that this bacterium was able to generate and conserve electrical power in different growth phases.…”
Section: Introductionmentioning
confidence: 99%
“…Genomic and genetic studies have assembled catabolic and electron-transport pathways in S. oneidensis MR-1 (Figure 1), and enzymes involved in these pathways are detailed elsewhere [17,18]. This bacterium prefers to utilize low molecular weight organic compounds, such as lactate, pyruvate and amino acids, as carbon and energy sources, while its ability to metabolize sugars is limited, except for the ability to utilize N-acetylglucosamine (NAG), an abundant sugar in the marine environment [19].…”
Section: Metabolic Characteristics Of S Oneidensis Mr-1 In Relation mentioning
confidence: 99%
“…In addition, it has also been shown that this engineered strain generates anodic current in glucose-supplemented BES via a working electrode (WE) poised at +0.6 V (vs. a standard hydrogen electrode, SHE) and produces lactate as an intermediate metabolite and acetate as the end product [21]. This engineered strain however does not grow on glucose under fermentative conditions (in the absence of electron acceptors), even though it has all enzymes necessary for completing the fermentative pathway from glucose to lactate [18]. Currently, it is not clear why the engineered strain cannot grow on glucose fermentatively, while understanding the reasons and development of methods to overcome this deficiency would be very important to utilize MR-1 and its derivatives in EF for producing value-added chemicals from biomass feedstocks.…”
Section: Metabolic Characteristics Of S Oneidensis Mr-1 In Relation mentioning
confidence: 99%
See 1 more Smart Citation
“…28 Recently, emerging technologies like bio-electrochemical systems have also been used to convert waste treatment into energy production. In this method, MRS ENERGY AND SUSTAINABILITY / / VO L U M E 7 / / e 3 3 / / www.mrs.org/energy-sustainability-journal ▪ 3 electrochemically active micro-organisms (e.g., Shewanella oneidensis and Geobacter sulfurreducens) are grown under electrochemical interactions with electrodes 29,30 to catalyze and oxidize organic matter to generate CO 2 , electrons, and protons. 30 The electrons are transferred to the anode, while the protons move through a membrane to the cathode, where they combine to release H 2 .…”
Section: Making Hydrogen From Biomassmentioning
confidence: 99%